Sistem Absensi Guru Berbasis Web Dengan Qr Code Pada Mi I’anatul Huda Serpong Utara - Nifa Abdillah, Muhamad Hafidz; Pambudi, Naufal; Bahri, Syaiful; Hardiansyah (shofanah Media Berkah, 2024)
Web-based teacher attendance system with QR Code at MI I'anatul Huda Serpong Utara is a system developed to facilitate the attendance process for teachers at the school. This system utilizes QR Code technology as a means to perform attendance quickly and efficiently. This system is built using the PHP programming language with the Laravel framework, and MySQL as a database. The main features of this system include (1) Creating a QR Code for each registered teacher. (2) Attendance feature using QR Code scan via smartphone device. (3) Recording teacher attendance history with information on date, time of entry, and time of return. (4) Teacher attendance reports that can be viewed by school administrators. (5) Teacher data management, such as adding, changing, and deleting teacher data. With this system, the teacher attendance process becomes more computerized and integrated, so that it can improve efficiency and accuracy in recording teacher attendance. In addition, this system can also assist schools in monitoring and managing teacher attendance more effectively